EFFECTIVENESS OF CASEIN PHOSPHOPEPTIDE STABILISED AMORPHOUS CALCIUM PHOSPHATE FOR TREATMENT OF WHITE SPOT LESIONS DEVELOPED AFTER ORTHODONTIC TREATMENT - Dr Musaab Hamid; Dr Naghma Parveen; Dr Rashid Iqbal; Dr Sajal Khan; Dr Javed Iqbal; Dr Talha Ashar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: This study was conducted to evaluate effectiveness of 10% casein phosphopeptide amorphous calcium phosphate on white spot lesions detected after initiation of orthodontic treatment using fixed applianceMethodology: The prospective study was conducted in Orthodontic Department, Nishtar Hospital, Multan from June 2022 to June 2023. The study included 50 patients who had at least one clinically visible white spot lesions on labial surface after debonding of orthodontic appliances. Subjects were divided into study group (n= 21) and control group (n=29). The participants in the study group were instructed to apply CPP–ACP cream (1g) on teeth once daily and to use fluoride tooth paste (1100 ppm F) once every morning for 4 weeks. The participants in study group were advised to use fluoride tooth paste twice daily.Results: The results showed that after the treatment, there was 58% decrease in lesion area in study group and 26% decrease in control group, and this difference was statistically different from the baseline (P 1. After 4 weeks, corresponding figures were 52.3% and 48.4% respectively. The difference between groups was not statistically significant.Conclusion: Casein phosphopeptide-stabilised amorphous calcium phosphate agent resulted in significant reduction and improvement in white spot lesions developed because of orthodontic brackets.